Bibliometric Analysis of Research Development on the Topic of State Border Development Using VosViewer - Daud, Restuardy; Bur, Marzidi; Sunarsi, Denok; Salam, Rudi (JOIV : International Journal on Informatics Visualization, 2024)
The development of national borders is a priority for a country in the interest of sovereignty and prosperity for its citizens. This study examines the development of research that takes the topic of developing national borders. The research aims to discover the development of the number of publications and maps of the development of publications over the last ten years on the topic of development in question. This research method uses descriptive bibliometric analysis, with metadata from 982 research publications sourced and processed from Google Scholar. The results showed that in the period 2012-2022, there was an increase in the development of publications, from 20 publications in 2012 (2.04%) to 182 publications in 2020 (18.54%), or an increase of 8 times compared to publications with the same topic in 2012. The development of mapping research publications based on keywords (co-occurrence) identified a description of the network of relationships between conceptions of national border development and related topics grouped into 10 clusters. Development is the main issue discussed in various studies in the last ten years. From the visualization overlay on co-occurrence, the keyword 'Development' is the most discussed topic and highlights the need for strengthening and improvement in managing national borders. This research also obtained several topics still open for researchers to develop, including infrastructure development and loci in border areas, which are interesting for future research topics.Â